Odpowiedzi

2010-02-15T12:06:40+01:00
5(3x+4)=32
15x+20=32
15x=32-20
15x=12/15
x=0.8


26-4x=12x-7( x+4)
26-4x=12x-7x-28
-4x-12x+7x=-28-26
-9x=-54/-9
x=6


3(x-1)=x-4
3x-3=x-4
3x-x=-4+3
2x=-1/2
x=-0.5


2x+1>9
2x>9-1
2x>8/2
x>4


-2(2x+3)≥6
-4x-6≥6
-4x≥6+6
-4x≥12/-4
x≤-3

4(4-3x)≥20(x+4)
16-12x≥20x+80
-12x-20x≥80-16
-32x≥64/-32
x≤-2

6(x+2)≤24
6x+12≤24
6x≤24-12
6x≤12/6
x≤2

8x-5<2(2-x)
8x-5<4-2x
8x+2x<4+5
10x<9/10
x<0.9


proszę : **
2010-02-15T12:15:33+01:00
5(3x+4)=32
15x+20=32
15x=32-20
15x=12
x=0,8



26-4x=12x-7( x+4)
26-4x=12x-7x-28
-4x-12x+7x=-28-26
-9x=-54
x=-6



3(x-1)=x-4
3x-3=x-4
3x-x=-4+3
2x=-1
x=-0,5



2x+1>9
2x>9-1
2x>8
x>4



-2(2x+3)≥6
-4x-6≥6
-4x≥6+6
-4x≥12
x≤-3



4(4-3x)≥20(x+4)
16-12x≥20x+80
-12x-20x≥80-16
-32x≥64
x≤-2



6(x+2)≤24
6x+12≤24
6x≤24-12
6x≤12
x≤2


8x-5<2(2+x)
8x-5<4+2x
8x-2x<4+5
6x<9
x<1,5